Pengaruh Celebrity Endorser dan Harga terhadap Keputusan Pembelian Produk Skincare Scarlett di Jakarta - Farikha Nuraida; Aris Hidayat (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The phenomenon of using celebrity endorsers as a marketing strategy has been rife in Indonesia, with many companies or brands using famous celebrities to promote their products and services. Celebrities have a huge influence on society, especially for their fans. Their lifestyle, image and opinions often become references for their fans in making decisions, especially purchasing decisions. To determine the effect of celebrity endoser and price on purchasing decisions for Scarlett Skincare products in Jakarta. The data collection method in preparing the thesis is the distribution of questionnaires and literature studies. The analysis method uses statistical quantitative analysis, using the SPSS version 26 application involving validity, reliability, classical assumption tests, hypothesis testing and the coefficient of determination. The results of the t test on X1 were obtained at 4.563> 1.984 had a positive effect on Y. There are also the results of the t test on X2 obtained at 6.676> 1.984 had a positive effect on Y. Then the results of the Anova F test of 104.536> F table 3.090 there is a partial influence between celebrity endorsers and prices on purchasing decisions.